US participation, permit allocation, and hot air supply - Gernot Klepper; Sonja Peterson (Institute for World Economics (IfW), 2002)
After Bonn and Marrakech it is likely that emission trading will be realized in the near future. Major influences on the permit market are the institutional details, the participation structure and the treatment of hot air. Different scenarios do not only differ in their implications for the demand and supply of permits and thus the permit price, but also in their allocative effects. Most repercussions can be expected to stem from the effects on the world markets for fossil fuel and especially the oil market. For example the withdrawal of the USA from the Kyoto Protocol and the allocation mechanism for the hot air in Russia, Ukraine and Eastern Europe influence the level of energy demand and gross and net energy prices which in turn change the production structure of energy intensive goods and influence welfare depending on whether a country is an energy net exporter or importer. In this paper we discuss different institutional designs for hot air trading combined with the US withdrawal and quantify the effects by using a computable general equilibrium model. Besides detailed results for the analyzed scenarios, two major findings are relevant for future studies on emission trading: First, marginal abatement cost curves are not as stable as presumed up to now. Second, we find that indeed the allocative repercussions of a scenario are to a large degree determined by its effects on world energy demand and world energy prices. Both findings imply that partial equilibrium models of permit trading that are based on marginal abatement curves ignore the important interaction between the permit market and the world energy markets.
Conference: 3rd Concerted Action for Tradable Permits (CATEP) Workshop on Global Trading, Institute for World Economics, Kiel, September 30 and October 1, 2002
Keywords: 330; Emissionshandel; Klimaschutz; Allokation; Wirtschaftspolitische Wirkungsanalyse; Simulation; Allgemeines Gleichgewicht; USA; Welt